Leading in health care organizations improving safety, satisfaction, and financial performance - Simons, Tony; Leroy, Hannes; Savage, Grant T. 1954- (Advances in health care management ;, 2013)
Health care organizations around the world are judged in terms of a health care triple bottom line: ensuring employee and patient safety, maximizing employee and patient satisfaction, and meeting financial goals. Given the increasing burden of chronic diseases, the increasing complexity of medical interventions, and the increasing costs of care, innovative leadership is required to achieve this triple bottom line. The 14th volume of the Advances in Health Care Management research series addresses the links between leadership and safety, satisfaction or financial performance in health care management by exploring questions such as the following: (1) How does leadership impact employee safety?(2) How does leadership affect patient safety?(3) How does leadership impact employee satisfaction?(4) How does leadership affect patient satisfaction?(5) How does leadership affect financial performance?(6) How do health care organizations deploy multi-level leadership to achieve safety goals? Satisfaction goals? Financial goals? Multiple goals?(7) How do health care organization leaders establish and maintain a safety culture? A patient-centered culture? A high performance culture? Combined cultures?